Progressive cardiac arrhythmias and ECG abnormalities in the Huntington's disease BACHD mouse model. (9th December 2019) - Zhu, Yujie; Shamblin, Isaac; Rodriguez, Efrain; Salzer, Grace E; Araysi, Lita; Margolies, Katherine A; Halade, Ganesh V; Litovsky, Silvio H; Pogwizd, Steven; Gray, Michelle; Huke, Sabine
Abstract: Huntington's disease (HD) is a dominantly inherited neurodegenerative disease. There is accumulating evidence that HD patients have increased prevalence of conduction abnormalities and compromised sinoatrial node function which could lead to increased risk for arrhythmia. We used mutant Huntingtin (mHTT) expressing bacterial artificial chromosome Huntington's disease mice to determine if they exhibit electrocardiogram (ECG) abnormalities involving cardiac conduction that are known to increase risk of sudden arrhythmic death in humans. We obtained surface ECGs and analyzed arrhythmia susceptibility; we observed prolonged QRS duration, increases in PVCs as well as PACs. Abnormal histological and structural changes that could lead to cardiac conduction system dysfunction were seen. Finally, we observed decreases in desmosomal proteins, plakophilin-2 and desmoglein-2, which have been reported to cause cardiac arrhythmias and reduced conduction. Our study indicates that mHTT could cause progressive cardiac conduction system pathology that could increase the susceptibility to arrhythmias and sudden cardiac death in HD patients.